'If you have a soul, you will volunteer at once': gendered expectations of duty to care during pandemics. Issue 2 (7th August 2012) - Godderis, Rebecca; Rossiter, Kate
Abstract Duty to care has been identified as a pressing ethical issue in contemporary discussions of pandemic preparedness; however, nuanced discussions of this complicated issue are relatively limited. This article presents historical data from the experience of the 1918 influenza pandemic in Brantford, Ontario in Canada, demonstrating that, in the face of an actual pandemic, the particular construction of duty to care as both moral and gendered meant that women were placed at a greater personal risk during this time. Given that women still dominate the front lines of healthcare work, we argue that it is critical for current stakeholders to reflect on how these historical patterns may be replicated in contemporary pandemic planning and response.